ORBITAL TUNING AND CORRELATION OF 1.7 M.Y. OF CONTINUOUS CARBON STORAGE IN AN EARLY MIOCENE PEATLAND - Large D.J.; Jones T.F.; Briggs J.; Macquaker J.H.S.; Spiro B.F. (My University, 2004)
Peatland is an important terrestrial carbon reservoir that contains >25% of soil carbon and accounts for 25% 38% of natural methane emissions. Most of this carbon is contained in postglacial boreal peat. Our understanding of the carbon cycle within this reservoir and its links to the atmosphere is therefore restricted to periods of <10 k.y. A record of the longer-term behavior of the peatland carbon reservoir under nonglacial conditions does, however, exist in thick lignite deposits formed over periods of >1 m.y. Spectral analysis of varying lignite color reveals that 120 m of early Miocene lignite from the Gippsland Basin, Australia, contains a 1.7 m.y. record of orbitally paced climate oscillations dominated by the response to obliquity. Use of the regular orbital signal indicates that the average long-term rate of peatland carbon accumulation recorded in the lignite is 27.5 g·m-2·yr-1. This rate is constant over periods of >100 k.y. and is independent of shorter-term, <10 k.y., fluctuations in climate and hydrology. Matching the lignite record to the theoretical insolation curve indicates that the lignite formed between 22.5 and 20.8 Ma. Contemporaneous long-term changes in lignite color and the 13C/12C ratios of marine foraminifera may relate to changing peatland methane flux and thus point to a link between terrestrial and marine carbon dynamics.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен